Flexible force/pressure sensor array - Tan, Yong Rui (2018)
Flexible electronics has attracted a lot of attention. One category of flexible electronic devices is flexible sensors that can detect physical quantities without affected by the shapes of the detectors. One broad application of this type of sensors is to detect force distribution or pressure distributions in 3 dimensions through contacting onto an object with an arbitrary shape. This requires the forces or pressure detections must be 3 D and the shapes of the sensors must be attached onto the object. In the project, the force or pressure detection will be realized using pressure sensitive rubber (PSR). When a force or pressure is exerted, the resistance of PSR would be changed. By monitoring the resistance variation, force or pressure strength can be determined. In this project, the fundamental calibration between the resistance variation and force or pressure strength will be carried out. A sensor array will be constructed from 4„e4, 8„e8 and 16„e16 PSR pixels and the signal from each pixel will be acquired and converted to digital signal in row-column scanning modes. The signals are required to illustrate on a display in a matrix of 4x4, 6x6 or 10x10 colour coded blocks.